2014
DOI: 10.3126/nepjoph.v6i2.11678
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations of childhood acute leukemia in a tertiiary level eye centre of Kathmandu, Nepal

Abstract: Introduction: In some instances, the understanding of the ocular manifestations in childhood leukemia is not only important to establish the diagnosis but also reflects the disease state and prognosis. Objective: To study the ocular manifestations of childhood acute leukemia among the children attending a tertiary-level hospital in Nepal. Materials and methods: A cross-sectional, descriptive study was undertaken at the B.P. Koirala Lions Centre for Ophthalmic Studies (BPKLCOS) and Kanti Children Hospital (KCH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
6
12
0
Order By: Relevance
“…In the current study, ophthalmic manifestations were present in 48.5% of patients with acute leukemia. The frequency of ocular signs in acute leukemia was similar to the studies of Koshy et al (51.9%) [10], Khadka et al (46%) [4], Gawai et al (52.23%) [5], and Dhasmana et al (45.1%) [7]. On the other hand, it was significantly less than those reported in the study of Eze et al (72.7%) [8].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In the current study, ophthalmic manifestations were present in 48.5% of patients with acute leukemia. The frequency of ocular signs in acute leukemia was similar to the studies of Koshy et al (51.9%) [10], Khadka et al (46%) [4], Gawai et al (52.23%) [5], and Dhasmana et al (45.1%) [7]. On the other hand, it was significantly less than those reported in the study of Eze et al (72.7%) [8].…”
Section: Discussionsupporting
confidence: 85%
“…Ophthalmic manifestations were more commonly seen as a consequence of secondary changes in systemic leukemia (83.3%) as compared to the direct ocular involvement in acute leukemia (16.7%). These findings were statistically significant and supported by the studies of Koshy et al [10], Khadka et al [4], Gawai et al [5], and Eze et al [8].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In large-scale surveys conducted in the past on acute myeloid leukemia, acute lymphatic leukemia, and chronic myeloid leukemia (Gordon et al, 2001; Russo et al, 2008; Khadka et al, 2014), the rate of ocular infiltration was not particularly high. In this survey, on the other hand, approximately half of the cases of ATL ocular lesions involved ocular infiltration.…”
Section: Discussionmentioning
confidence: 98%
“…Ophthalmic manifestations have been reported in the literature with different prevalence from study to study, ranging from 24% to 70% [4,[8][9][10][13][14][15][16][17]. Also, some studies that have been done in Saudi Arabia reported prevalence ranging from 35%-54%; however, these studies are old and published in the '90s [13][14][15].…”
Section: Discussionmentioning
confidence: 99%